Optimalisasi Kinerja Sistem Informasi Manajemen Melalui Penerapan Database yang Efektif - Sari, Mutia Indah; Nasution, Muhammad Irwan Padli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the impact of applying effective database design in optimizing the performance of Management Information System (MIS). A common problem faced by MIS in various organizations is the inefficiency of data processing caused by poorly structured database design, unoptimized queries, and weak data management, wich affects the consistency and validity of information. Trought a literature review and comparative analysis approach, this research shows that improving database structure design, implementing query optimization strategies, and systematic data management can enhance system performance by up to 40%. This study emphasizes the importance of a well-structured database as a strategic foundation to support data-driven desicion-making in modern organizational environments.